2022
DOI: 10.3390/ijms23031500
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Epigenetics of Bone Remodeling and Metabolic Bone Diseases

Abstract: Bone metabolism consists of a balance between bone formation and bone resorption, which is mediated by osteoblast and osteoclast activity, respectively. In order to ensure bone plasticity, the bone remodeling process needs to function properly. Mesenchymal stem cells differentiate into the osteoblast lineage by activating different signaling pathways, including transforming growth factor β (TGF-β)/bone morphogenic protein (BMP) and the Wingless/Int-1 (Wnt)/β-catenin pathways. Recent data indicate that bone rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 203 publications
0
27
0
Order By: Relevance
“…The methylation status determines the propensity of bone marrow-derived MSCs to differentiate towards osteoblasts, which may be associated with hypomethylation of the promoter regions of the osteogenic genes RUNX2 and OCN, and higher expression of the corresponding mRNAs. In addition, methylation regulation of the Wnt/b-catenin signalling pathway and the RANKL/RANK/ OPG system also plays an important role in bone regeneration (Oton-Gonzalez et al, 2022). The studies related to DNA methylation in periapical inflammation are currently inadequate, and the elucidation of the relevant mechanisms depends on further studies.…”
Section: Dna Methylationmentioning
confidence: 99%
“…The methylation status determines the propensity of bone marrow-derived MSCs to differentiate towards osteoblasts, which may be associated with hypomethylation of the promoter regions of the osteogenic genes RUNX2 and OCN, and higher expression of the corresponding mRNAs. In addition, methylation regulation of the Wnt/b-catenin signalling pathway and the RANKL/RANK/ OPG system also plays an important role in bone regeneration (Oton-Gonzalez et al, 2022). The studies related to DNA methylation in periapical inflammation are currently inadequate, and the elucidation of the relevant mechanisms depends on further studies.…”
Section: Dna Methylationmentioning
confidence: 99%
“…It regulates the T and B immune response through the TGFB1: CXCR4 interaction ( 35 ). It mediates osteoclast activation in bone remodeling and tumor angiogenesis ( 36 , 37 ). Together, we noticed that C14 and C25 acted as a bridge between tumor components and nontumor components.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been acknowledged that the tendency of MSCs from different origin towards certain cell fate is also dictated by the 12 Stem Cells International DNA methylation status. For example, hypomethylation of osteogenic genes was found in BM-MSCs, but in AD-MSCs, adipogenic genes were hypomethylated instead [72]. Yang et al [73] demonstrated that DNMT1 promoted adipogenesis at early stage but not inhibiting this process at late stage, suggesting DNMT1 governed adipogenic commitment in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%